A Plasma α-Tocopherome Can Be Identified from Proteins Associated with Vitamin E Status in School-Aged Children of Nepal. Issue 12 (14th October 2015) - West, Keith P; Cole, Robert N; Shrestha, Sudeep; Schulze, Kerry J; Lee, Sun Eun; Betz, Joshua; Nonyane, Bareng AS; Wu, Lee S-F; Yager, James D; Groopman, John D; Christian, Parul
Abstract: Background: The term vitamin E describes a family of 8 vitamers, 1 of which is α-tocopherol, that is essential for human health. Vitamin E status remains largely unknown in low-income countries because of the complexity and cost of measurement. Quantitative proteomics may offer an approach for identifying plasma proteins for assessing vitamin E status in these populations. Objective: To improve options for vitamin E status assessment, we sought to detect and quantify a set of plasma proteins associated with α- and γ-tocopherol concentrations in a cohort of 500 rural Nepalese children aged 6–8 y and, based on nutrient-protein associations, to predict the prevalence of vitamin E deficiency (α-tocopherol <12 μmol/L). Methods: Study children were born to mothers enrolled in an earlier antenatal micronutrient trial in Sarlahi District, Nepal. Plasma α- and γ-tocopherol concentrations were measured by high-performance liquid chromatography. Plasma aliquots were depleted of 6 high-abundance proteins, digested with trypsin, labeled with isobaric mass tags, and assessed for relative protein abundance by tandem mass spectrometry. Linear mixed-effects models were used to evaluate the association between α-tocopherol status and relative protein abundance and to predict deficiency. Results: We quantified 982 plasma proteins in >10% of all child samples, of which 119 correlated with α-tocopherol (false discovery rate, q < 0.10). Proteins were primarily involved in lipid transport, coagulation, repair, innate host defenses, neural function, and homeostasis. Six proteins [apolipoprotein (apo)C-III; apoB; pyruvate kinase, muscle; forkhead box 04; unc5 homolog C; and regulator of G-protein signaling 8] explained 71% of the variability in plasma α-tocopherol, predicting an in-sample population prevalence of vitamin E deficiency of 51.4% (95% CI: 46.4%, 56.3%) compared with a measured prevalence of 54.8%. Plasma γ-tocopherol was associated with 12 proteins ( q < 0.10), 2 of which (apoC-III and Misato 1) explained 20% of its variability. Conclusions: In this undernourished population of children in South Asia, quantitative proteomics identified a large plasma α-tocopherome from which 6 proteins predicted the prevalence of vitamin E deficiency. The findings illustrate that protein biomarkers, once absolutely quantified, can potentially predict micronutrient deficiencies in populations. The maternal micronutrient supplementation trial from which data were derived as a follow-up activity was registered withclinicaltrials.gov as NCT00115271.